2022
DOI: 10.1038/s41598-021-03863-y
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone-mediated regulation and functions of miR-218-5p in rat brain

Abstract: Chronic stress is one of the key precipitating factors in major depressive disorder (MDD). Stress associated studies have underscored the mechanistic role of epigenetic master players like microRNAs (miRNAs) in depression pathophysiology at both preclinical and clinical levels. Previously, we had reported changes in miR-218-5p expression in response to corticosterone (CORT) induced chronic stress. MiR-218-5p was one of the most significantly induced miRNAs in the prefrontal cortex (PFC) of rats under chronic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…It has earlier been shown that the other member of the SLIT gene family, i.e., SLIT2, harbors intronic miR-218-1, which encodes the other isoform of the miR-218 family (miR-218-1-3p). It is interesting to highlight that both isoforms are rooted in the Slit-Robo signaling axis with a functional role in depression-/anxiety-like behaviors as previously reported in adult mice [ 33 ]. The secreted Slit ligands and their Robo receptors constitute a signaling pathway that controls the directed migration of neurons and vascular endothelial cells during embryonic development.…”
Section: Emerging Role Of Mir-218 In Disease Pathogenesismentioning
confidence: 84%
See 4 more Smart Citations
“…It has earlier been shown that the other member of the SLIT gene family, i.e., SLIT2, harbors intronic miR-218-1, which encodes the other isoform of the miR-218 family (miR-218-1-3p). It is interesting to highlight that both isoforms are rooted in the Slit-Robo signaling axis with a functional role in depression-/anxiety-like behaviors as previously reported in adult mice [ 33 ]. The secreted Slit ligands and their Robo receptors constitute a signaling pathway that controls the directed migration of neurons and vascular endothelial cells during embryonic development.…”
Section: Emerging Role Of Mir-218 In Disease Pathogenesismentioning
confidence: 84%
“…The characteristic stem-loop structure of precursor miR-218 has been shown on Figure 2 a. The transcriptional origin of miR-218 has been mapped on two separate loci, miR-218-1 and miR-218-2 and found to be located at the introns of SLIT2 and SLIT3 genes, respectively [ 33 ]. More specifically, miR-218-1 is located within intron 15 of the SLIT2 gene, and mir-218-2 is present within intron 14 of the SLIT3 gene.…”
Section: Emerging Role Of Mir-218 In Disease Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations